A Time Series Analysis of Forest Cover and Land Surface Temperature Change Over Dudpukuria-Dhopachari Wildlife Sanctuary Using Landsat Imagery - Hasnat, G. N. Tanjina (Frontiers in Forests and Global Change, 2021)
Forest cover change is an important criterion as it effects on the environmental balance and land surface temperature is the parameter to understand the global warming. Spatio-temporal change of forest cover can be detected and land surface temperature can be retrieved by applying remote sensing technology. The present study aimed to detect the forest cover change and retrieve the land surface temperature of Dudpukuria-Dhopachari Wildlife Sanctuary (DDWS), Bangladesh. The images when available collected purposively in the similar time period - 1990 (5th March 1990), 2000 (5th February 2000), 2010 (24th February 2010) and 2020 (23rd March 2020) to avoid the biasness. Unsupervised classification was applied over the images Landsat 4-5 Thematic Mapper (TM), 7 Enhanced Thematic Mapper Plus (ETM+) and 8 Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) data for detecting forest cover change. To retrieve the land surface temperature Mono Window Algorithm (MWA) method was applied over the similar images. Maximum forest degradation observed in 2010 and the change found 17% from 1990. After 2010, the forest started to flourish. Land surface temperature dramatically changes over time. The highest value of temperature observed in 2020 (320C) and it was changed 7.70C from that of 1990 (29.20C). In every 10 years, the highest value of temperature changes found 2.30C-30C. The land surface temperature found as the effect of global warming rather than forest cover change as forest cover improved in last decade but land surface temperature increased at the same time.